1996
DOI: 10.1021/bc960015f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 17β-Hydroxyandrost-4-en-3-one−7α-(Biotinyl-6-N-hexylamide), a Conjugate Useful for Affinity Chromatography and for Testosterone Immunoassays

Abstract: We describe the synthesis of 17 beta-hydroxyandrost-4-en-3-one-7 alpha-(biotinyl-6-N-hexylamide) from 17 beta-hydroxyandrost-4-en-3-one (testosterone) via copper-catalyzed 1,6 Michael addition of a 6-(tertbutyldimethylsilyloxyhexyl) chain to 6-dehydrotestosterone 17 beta-acetate. After chromatographic separation of the 7 alpha-isomer from the alpha / beta mixture and cleavage of the silyl ether, the alcohol was oxidized to the 6-hexanal side chain and then subjected to reductive amination. The resulting primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…This presentation describes synthetic approaches for the biotinylation of T at the following positions: 3, 7R, 17R, and 19. Besides the synthetic pathways for the aliphatic 7R-biotinylated derivatives using the 1,6 Michael addition of hydroxylalkyl-modified Grignard compounds to 17-acetoxy-6,7dehydro-T [already described by our group (Luppa et al, 1996)], which represents a nonstereoselective reaction, the 1,6-addition of the 9-t-butyldimethyl-silyloxy-5-oxanonyl-and 13-t-butyldimethylsilyoxy-7-oxa-tridecyl-magnesium bromides provides ether chain-linked 7R-derivatives with high R-stereoselectivity. 3-Biotinylated T derivatives are available by the well-known hydrazone formation procedures at the 3-oxo position in an one pot reaction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This presentation describes synthetic approaches for the biotinylation of T at the following positions: 3, 7R, 17R, and 19. Besides the synthetic pathways for the aliphatic 7R-biotinylated derivatives using the 1,6 Michael addition of hydroxylalkyl-modified Grignard compounds to 17-acetoxy-6,7dehydro-T [already described by our group (Luppa et al, 1996)], which represents a nonstereoselective reaction, the 1,6-addition of the 9-t-butyldimethyl-silyloxy-5-oxanonyl-and 13-t-butyldimethylsilyoxy-7-oxa-tridecyl-magnesium bromides provides ether chain-linked 7R-derivatives with high R-stereoselectivity. 3-Biotinylated T derivatives are available by the well-known hydrazone formation procedures at the 3-oxo position in an one pot reaction.…”
Section: Discussionmentioning
confidence: 99%
“…High specificity is achievable only if the tracer resembles in structure to the native steroid (Chames and Baty, 1998). Recently, we showed that the introduction of a biotin label to E1 at the ring position 6R and to T at the position 7R leads to negligible alterations in comparison to the structure of the respective steroidal hapten (Luppa et al, 1994(Luppa et al, , 1996. These characteristics allow sensitive and reproducible determinations of E1 and T over large dynamic ranges (Luppa et al, 1995(Luppa et al, , 1997.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The introduction of an alkenyl chain was carried out by adding to unsaturated ketone II the Grignard reagent prepared from 5-bromopentene [9] under catalysis with copper bromide complex with dimethyl sulfide [7,10,11]. Adding to the reaction mixture the trimethylsilyl chloride (TMSCl) and the hexamethylphosphoramide (HMPA) [12] we raised the yield of adduct IV from 85 to 95%.…”
mentioning
confidence: 99%